Estudo de efetividade de um programa de atendimento psicossocial para adolescentes em vulnerabilidade social - Paula, Tassiane Cristine Santos de [UNIFESP] (2016)
Study the adherence to psychosocial care program and evaluate the effectiveness of this program with adolescents in social vulnerability for keep or return in school . Method: Naturalistic retrospective follow-up of 282 adolescents attended 2007 to 2012, in multidisciplinary intervention program with assumptions oh Harm Reduction approach. The condition of being studying after six months was evaluated among the individuals who adhered and those leaving the program. The intervention effect was evaluated by logistic regression models. Results: 55% boys; 60% urban area and 40% rural; 24% family income below of the poverty line; 23% school dropouts; 59% gap with school-age series; and 50% problem at school. The association between adherence to the intervention and be studying after 6 months was significant Odds = 6,86 (IC 95% - 2,70 ? 17,38), after controlling of the effect of others variables associated with outcome. Conclusion: The study showed that psychosocial care program, multidisciplinary preventive character and health promoter is effective in rehabilitation and school continuity adolescents in social vulnerability.